The Relationship of Dynamic Balance with Football Skill: A Correlation Study in Under-15 Football Athletes - Pratomo, Donny; Razali, Razali; Syamsulrizal, Syamsulrizal; Akbari, Myrza (Department of Physical Education, Sport, Health and Recreation, 2021)
Football skills are one of the fundamental aspects that must be possessed by football players. In addition, to support football skills, football players must be equipped with the ability to be in good physical condition. Based on theoretical studies, movement in football is dominated by dynamic movements so that dynamic balance is one of the important aspects in supporting football skills. This study aims to determine the relationship between dynamic balance and football skills. This study uses a quantitative approach to the type of correlational research. The population of this study was the Junior Players of the Persati Aceh Tamiang Club, totaling 36 athletes (total sampling). The data collection techniques were as follows: (1) dynamic balance using the